Algunas consideraciones arqueológicas sobre la vivienda doméstica en Pompeya - Funari, PEDRO PAULO A. (Gerión. Revista de Historia Antigua, 2001)
Pompeian dwelling have been studied for a long time. However, most approaches are grounded on common sense and the acritical acceptance of data found in the literary sources. This paper aims at discussing in a critical way some recent and widely accepted studies on the subject of both Pompeian dwellings and the Roman society in general. We focus on the analytical tools archaeology can provide for a better understanding of ancient life.